Market Basket Analysis dengan Perbandingan Metode Apriori dan FP-Growth Pada Data Transaksi XYZ - Rizki Nofrian Wahyudi; Dyah Erny Herwindiati; Janson Hendryli (Jurnal Ilmu Komputer dan Sistem Informasi, 2023)
Technology is currently advancing quickly, allowing all organizations to grow their networks with its aid and create sales methods that now rely on technology to aid in making the proper judgments. When saved transaction data is accessible, every business will be able to implement its marketing strategy to maximize client transactions. use it to your advantage. Analysis of the market basket using the FP-Growth and a priori algorithm in transactions that aid in strategic planning and business product structuring. The FP-Growth algorithm and the Apriori algorithm work well together. One can evaluate the effectiveness of the employment of the a priori algorithm and the FP-Growth algorithm by applying both of them